Comparing plastic surgery and otolaryngology surgical outcomes and cartilage graft preferences in pediatric rhinoplasty: A retrospective cohort study analyzing 1839 patients. Issue 25 (25th June 2021) - Doval, Andres F.; Ourian, Ariel; Boochoon, Kieran S.; Chegireddy, Vishwanath; Lypka, Michael A.; Echo, Anthony
Abstract : Abstract: Rhinoplasty in children has raised concerns about its safety in the pediatric population. There is scarcity of evidence describing outcomes and surgical techniques performed in pediatric rhinoplasty. We analyzed post-operative complications and cartilage preferences between plastic surgeons and otolaryngologists. Data was collected through the Pediatric National Surgical Improvement Program from 2012 to 2017. Current Procedure Terminology codes were used for data extraction. Patients were grouped according to type of rhinoplasty procedures (primary, secondary, and cleft rhinoplasty). A comparison between plastic surgeons and otolaryngologists was made in each group in terms of postoperative complications. Additionally, a sub-group analysis based on cartilage graft preferences was performed. During the study period, a total of 1839 patients underwent rhinoplasty procedures; plastic surgeons performed 1438 (78.2%) cases and otolaryngologists performed 401 (21.8%) cases. After analyzing each group, no significant differences were noted in terms of wound dehiscence, surgical site infection, readmission, or reoperation. Subgroup analysis revealed that plastic surgeons prefer using rib and ear cartilage, while otolaryngologists prefer septal and ear cartilage. The analysis of 1839 pediatric patients undergoing three types of rhinoplasty procedures showed similar postoperative outcomes, but different cartilage graft utilization between plastic surgeons and otolaryngologists.